ORGANIZATIONAL RESILIENCE AND BUSINESS COMPETITIVENESS OF MYPES IN AN INDUSTRIAL PARK IN LIMA, 2023-2025 - Cervantes Ramón, Edgard Francisco (2025)
The objective of this article was to determine the level of relationship between organizational resilience as an internal factor of the business competitiveness of Mypes in an Industrial Park in Lima. The survey was applied to a population that was made up of 384 managers and administrators of micro and small businesses and the sample was 52 Mypes. The results achieved demonstrate a high level of organizational resilience of 51.92%, as well as being able to reach a 63.46% level of regular business competitiveness; in the hypothesis test a bilateral asymptotic significance of p = 0.000, in addition to a high positive level of 0.762 of Spearman’s rho correlation. In conclusion, it was  demonstrated that organizational resilience is an internal factor that is directly and significantly related to the business competitiveness of the Mypes of an Industrial Park in Lima.